Service Quality dalam Membangun Competitive Advantage di Pondok Pesantren Nurul Jadid - Mashur Imam; Abdullah (Nusantara Journal of Islamic Studies, 2022)
This study describes service quality in building a competitive advantage in Nurul Jadid Islamic Boarding School. This research uses a qualitative case study approach. The data is obtained from observations and interviews. The resource persons in this study were seven people and consisted of the head of the Nurul Jadid Islamic boarding school, the head of the bureau leadership, bureau staff, students, guardians of students, alumni and the community around the Nurul Jadid Islamic boarding school. The data analysis uses Miilles and Hubberman's data reduction, data display and data verification. The results obtained from the implementation of service quality in building a competitive advantage at the Nurul Jadid Islamic Boarding School are (1) Tangible: tangible services such as E-Bekal services, BPS, visiting students, goods deposit services, and so on, (2) Reliability: service in the form of reliability such as TOEFL test services, service SOPs, service regulations, teacher centralization, etc., (3) Responsivness: services that are responsive or complaints from guardians in the form of guardian groups, (4) Assurance: health insurance, job security and pensions, (5 ) Empathy: the role of guardian for students